(3GdbVGjG GdEbJUGOjI aj GdUMGaI GdecJhHI GdLRGFQjI (B/s - (3YdGd, EjeGfs ((3GdLRGFQ (B:s (3OGQ heVI ddfTQ hGdJhRjY h GdJQLeI ,s, 2022)
(3jJeMhQ ehVhY GdOQGSI Mhd GdeYGdLI GdEYdGejI ddbVGjG GdEbJUGOjI aj GdUMGaI GdecJhHI GdLRGFQjI h h JMOjOG UMjaI GdNHQ NdGd GdaJQI GdeeJOI ef (B01 (3GcJhHQ (B2017 (3Gdi(B31 (3eGQS (B2018 (3h gj OQGI JMdjdjI JSYi Gdi JSdjW GdVhA Mhd cjajI eYdLI GdUMGaI GdecJhHI GdNGUI ddbVGjG GdEbJUGOjI h Pdc ef NdGd cTa OQLI GgJeGe jhejI GdNHQ HgPg GdbVGjG HGYJHGQgG GMO GdUMa GdNGUI GdGcKQ GfJTGQG h ebQhFjI HGdGVGaI Gdi GdJYQa Ydi eOi GdJRGegG HeSDhdjJgG GdGLJeGYjI h JeTcgG HGNdGbjGJ GdegfI h bO Je GdGYJeGO Ydi GdefgL GdeSMj HZQV JMdjd h JaSjQ eNJda eYWjGJ GdeGOI GdGYdGejI GdeOQhSI TcdG h eVehfG h Yf WQjb GSJNOGe GOGI JMdjd GdeVehf cGOGI QFjSjI dGcJTGa SeGJ h eMJhi h Tcd GdbVGjG GdEbJUGOjI aj GdUMGaI GdecJhHI GdNGUI ceG GSJYfG HGdebGHdI cGOGI KGehjI ef GLd LeY GdeYdheGJ h GKQGA GdOQGSI GdcTa Yf eOi MVhQ GdbVGjG GdGbJUGOjI ebGQfI jGdbVGjG GdGNQis
Keywords: (3GdLRGFQs; (3GdEYdGe GdEbJUGOjs; (3GdUMGaI GdLRGFQjIs; (3GdUMGaI GdecJhHIs